A Conceptual Review of Tsunami Models Based on Sumatera-Andaman Tsunami Event - ., NH Mardi, MA Malek, MS Liew, HE Lee (2015)
Sumatra-Andaman tsunami was categorized as the third worst tsunami by the United State Geology Survey (USGS). The tsunami was triggered at 00:58:53 UTC by a massive earthquake with recorded moment magnitude of 9.1 at the west coast of North Sumatera. Malaysia is one of the countries affected by the 26th December 2004 tsunami. Others countries also affected by this event include Indonesia, Sri Lanka, Thailand, India, Maldives, Myanmar, Bangladesh, Somalia, Tanzania, Kenya and Yemen. The earthquake epicenter is located where the Indian Plate subducted under the Burma Plate. This tsunami event has raised the awareness of many people. Today, several tsunami numerical models have been developed to model and forecast tsunami events in the future. This paper reviews five tsunami numerical models namely TUNA, TUNAMI, COMCOT, MOST and ANN Tsunami Forecast. Most of these models have been used by other researchers to perform tsunami simulation based on Sumatera-Andaman tsunami event. Each model have their own similarities, differences and limitations. A non-mathematically intensive approach is employed to choose a suitable tsunami numerical model for the case study in Malaysian offshore areas. Future studies will be conducted using one of the tsunami numerical models.